The role of introductory alarm calls for song discrimination in Ficedula flycatchers. (July 2021) - Bliard, Louis; Qvarnström, Anna; Wheatcroft, David
Abstract : Assortative mating depends on species distinctiveness in mating traits and preferences, which can be challenging to maintain when traits and/or preferences are learned. This is because learning may cause individuals to copy heterospecific signals. Juvenile songbirds possess innate sensory biases favouring them to learn and to prefer conspecific songs, but the effectiveness of these biases relies on consistent and sufficient differences between the songs produced by different species. However, mating signals, including learned songs, sometimes converge in sympatry, and the species-specific cues that individuals use to shape their preferences are often unknown. In Ficedula flycatchers, a stereotyped and highly species-specific alarm call is often incorporated as the first syllable of their songs. However, where the two species co-occur, pied flycatchers, Ficedula hypoleuca, learn to incorporate the introductory calls of the closely related collared flycatcher, Ficedula albicollis, into their songs. In this study, we investigated the role of introductory alarm calls for song discrimination in collared flycatchers, using playback experiments of both manipulated and unmanipulated songs on adults and nestlings within the hybrid zone of Öland, Sweden. We predicted that the introductory alarm call would be sufficient to trigger song responses, such that adults and nestlings would respond similarly to song phrases including the call, whether it is followed by conspecific or heterospecific notes. Our results provide evidence that the introductory alarm call is sufficient to trigger song discrimination in nestlings, but not in adult males, potentially due to their greater experience with songs and, therefore, subtler discrimination. Altogether, this study highlights the often-overlooked importance of calls within or associated with songs. Highlights: Collared flycatchers often start their songs with an alarm call. The alarm call seems sufficient to drive song responses in nestlings. We argue that the call could guide learning onto appropriate songs. However, the call alone is unlikely to be sufficient for discrimination in adults. We discuss the broader implication of incorporation of calls into songs.